Equilibrium in financial markets with adverse selection - Tuomas Takalo; Otto Toivanen (Bank of Finland, 2003)
We study a financial market adverse selection model where all agents are endowed with initial wealth and choose to invest as entrepreneurs or financiers, or not to invest.We show that often a lack of outside finance leads to the emergence of financial markets where availability of outside finance leads to autarky.We find that i) there exist Pareto-efficient and inefficient equilibria; ii) adverse selection has more severe consequences for poorer economies; iii) increasing initial wealth may cause a shift from Pareto-efficient to inefficient equilibrium; iv) increasing the proportion of agents with positive NPV projects causes a shift from inefficient to efficient equilibrium; v) equilibrium financial contracts are either equity-like or 'pure' debt contracts; vi) agents with negative (positive) NPV projects earn rents only in (non-)wealth-constrained economies; vii) agents earn rents only when employing pure debt contracts; and viii) removing storage technology destroys the only Pareto-efficient equilibrium in non-wealth-constrained economies.Our model enables analysis of various policies concerning financial stability, the need for sophisticated financial institutions, development aid, and the promotion of entrepreneurship.
URN:NBN:fi:bof-20140807264
Keywords: D58; G14; G20; G28; G32; 330; financial market efficiency; adverse selection; financial contracts; creation of firms